Developing quadcopter using Pixhawk 2.4.8 for enhancing atmospheric physics learning - Wayan Suparta (International Journal of Electronics and Telecommunications)
Implemented project-based learning using drones is more fun and the concepts delivered are easily understood by students. This research has built a DIY drone using an F450 quadcopter to improve the quality of the learning process such as basic concepts of atmospheric physics. The main system of the drone is a Pixhawk 2.4.8 flight controller where the system is set up via Mission Planner to work on autopilot. For atmospheric physics learning, atmospheric data such as temperature, relative humidity, and air pressure is collected using BME280 sensors on the drone and on the ground. The sensor is controlled by Arduino Uno and a data logger has also been developed to store data into a Micro SD card for post hoc analysis. Once the drone is tested for flight stability, it can be applied to measure atmospheric parameters including flight altitude and precipitable water vapor. With this development, the system can be utilized to quantitatively show the relationship between atmospheric parameters and ultimately can predict other related parameters as well as able to provide interpretation of measurement results as evidence of improved understanding.